Novel microbially transformed bile acids: Biosynthesis, structure, and function - Qi Zhao; Zilei Duan; Ren Lai; Pengcheng Ma (Pharmacological Research)
The roles of gut microbiota and microbially modified bile acids in human health have become widely recognized. In the last five years, various microbially modified bile acids (e.g., proteinogenic amino-conjugated bile acids, polyamine-conjugated bile acids, neuroactive amine-conjugated bile acids, methylcysteamine-conjugated bile acids, acylated bile acids, dicarboxylic acid-conjugated bile acids, lithocholic acid (LCA) derivatives) were identified and evaluated, which greatly enriched the mammalian bile acid pool and the bioactivity of bile acids. The structure, enzyme, function, clinical reports of these bile acids, and the bacteria to produce these bile acids were summarized in this review. These novel bile acids had various functions including immunoregulation, receptor regulator, antimicrobial activity, and microbial communities regulating effect. 70, 4, 1, 11, 19, 41, 43, 9, 10 species were observed to produce proteinogenic amino-conjugated bile acids, neuroactive amine-conjugated bile acids, methylcysteamine-conjugated bile acids, acylated bile acids, dicarboxylic acid-conjugated bile acids, 3-oxoLCA, isoLCA, 3-oxoalloLCA, and isoalloLCA, respectively. The current review has shed new light on discovering new bile acid derivatives as drug candidates. These microbially modified bile acids may play important roles in disease such as sleeve gastrectomy, fatty liver, inflammatory bowel disease, cystic fibrosis, and type 2 diabetes, which may also participate in normal physiological processes such as growth of infants, longevity, and dietary habits.